Concurrent Ramsay Hunt syndrome and disseminated herpes zoster in a patient with relapsed chronic lymphocytic leukemia. (2016) - Chen, Ishita; Fohtung, Raymond B.; Oughli, Hanadi Ajam; Bauer, Robert; Mattar, Caline; Powderly, William G.; Thoelke, Mark S.
Abstract: Ramsay Hunt Syndrome (RHS) is a rare complication of latent varicella-zoster virus (VZV) infection that can occur in immunocompetent host. It usually involves ipsilateral facial paralysis, ear pain and facial vesicles. Disseminated herpes zoster is another complication of VZV infection typically seen in immunocompromised hosts. We describe a patient with relapsed chronic lymphocytic leukemia (CLL) who presented simultaneously with RHS and disseminated herpes zoster. While other complications have been documented to coexist with RHS, to our knowledge, this is the first reported case in the literature of concurrent RHS with disseminated herpes zoster.